Improvement of Arabic speaking skills among non-Arabic students through role-play activities - Salem Abdulhafid, Karima Aboubakr; Mustapha, Nik Farhan; Hassan, Abd Rauf; Ismail, Muhd Zulkifli (Human Resources Management Academic Research Society (HRMARS), 2024)
Mastering speaking skills poses a considerable challenge for students learning a foreign language, especially when doing so in their hometown, far from an authentic language environment. This study aimed to assess students' speaking proficiency and analyze the impact of role-playing activities on their skills. Following an experimental method, 40 male and female students majoring in Arabic at the University of Putra Malaysia (UPM) were selected. The study employed an applied model of speaking activities, with a focus on "roleplaying" as a teaching method enabling students to practice daily life interactions in the classroom. Two sets of pre-tests and post-tests served as instruments for data collection. The analysis revealed significant differences in speaking proficiency before and after the activities when comparing pre-test and post-test results. The findings demonstrated a marked improvement in students' conversational skills after engaging in role-playing activities during lessons, resulting in enhanced proficiency and confidence in Arabic conversation. The study also confirmed that integrating role-playing as a linguistic activity in group interactions between students and teachers facilitated the expression of feelings and boosted students' self-confidence.